The effects of shock waves on the rat fetus - Yalçın, Orhan; Tahmaz, Lütfi; Yumbul, Zühal; Bilgiç, İdris (My University, 1998)
There is an ongoing controversy regarding shock wave lithotripsy (SWL) con-traindicated during pregnancy (1, Z). While the effects of shock waves on a variety of cells in both clinical and experimental studies are well documented, their effects on the fetus remain to be clarified. In this study, we investigated the effects of SWL on the rat fetus. On the 8th, 1 lth, 14th and 17th days of pregnancy, 100, 250 or 500 shock waves were produced with a Multimed 2001 ELMED Systems Lithotriptor. In ongoing pregnancy, the effects of SWL on fetuses ranged from mild in early pregnancy to moderate and fatal later. No viable fetuses were determined in the latest period of pregnancy in rats taking 500 shocks. Histological changes were observed in the brain, lungs and subcutaneous tissue. Fusion and necrosis were determined in many of the dead fetus-es. Our study demonstrates that SWL- causes fetal damage and death during the late period of pregnancy in rats. Additional studies on the use of SWL during pregnancy mustbe done with later-generation lithotriptors.
Keywords: Tıbbi Araştırmalar Deneysel; Kadın Hastalıkları ve Doğum; Genel ve Dahili Tıp; Pediatri